Detection The Prevalence of Adhesins and Extracellular hydrolytic enzymes genes in Candida albicans Biofilm Formation - Mohammed , Najwan Abbas; Ajah , Hamzia Ali; Abdulbaqi , Nemat Jamel (Iraqi Journal of Science, 2021)
Biofilm formation (BF) is one of the most important virulence factors ofCandida spp. The aim of this study was to detect the prevalence of genesresponsible in biofilm formation of C. albicans by conventional PCR technique.Among 49 vaginal specimens (VC), C. albicans was the most predominant speciesin percentage 22/49 (45%) and 27(55%) were non albicans. Out of 47 oralspecimens (OS), 22/47(47%) were C. albicans, whereas 25(53%) were non albicans.At the present study; all C. albicans were biofilm producers with variable strength,out of 44 BF producers, 18 (40.9%) were low biofilm (LBF) with significantdifferences (P<0.05) between HVS and OS, 25 (56.8%) moderate or high biofilm(HBF) and just one isolate from oral was strong (very high) biofilm in percentageabout 2.3% with no significant differences between HVS and OS.Molecular study of virulence genes correlated with biofilm C. albicans showthat HWP1, ALS1, ALS3, SAP5, PLB1 and LIP8 genes were detected in 100% of C.albicans from vaginal and oral infections.